INCREMENTO DOS TEORES DE CARBONO EM NEOSSOLO QUARTZARÊNICO DE CERRADO COM O USO DE ADUBOS VERDES - machado, Isabela; Garcia, Maiara Fernanda; Paulino, Leonardo; Candido, Simone; Feliciani, Giselle; Marques, Jefferson Rogério (ANAIS DO ENIC, 2018)
-